2018
DOI: 10.3855/jidc.8081
|View full text |Cite
|
Sign up to set email alerts
|

Use of carbapenems and glycopepdides is significant risk for multidrug resistant Acinetobacter baumannii infections

Abstract: Introduction: Multi-drug resistant Acinetobacter baumannii (MDR-Ab) infections are an important healthcare problem globally. The aim of this study was to evaluate risk factors associated with MDR-Ab infections in hospitalized patients in Turkey. Methodology: A case-control study was performed in a tertiary care 1,303-bed university hospital, among case patients with MDR-Ab infections. The hospital records of case and control patients were retrospectively evaluated over a year. Patients who were hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In a study comparing Acinetobacter pneumonia with pneumonia due to other agents, when patients had taken appropriate antibiotic therapy, there was no difference in mortality rate between two groups. Also in our patients, between the antibiotic regimens and mortality rate were not significantly different [21]. Antibiotic treatment course for VAP is usually 7 days and it has been shown that this timing schedule has not been associated with higher mortality rate in comparison with longer periods [12].…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…In a study comparing Acinetobacter pneumonia with pneumonia due to other agents, when patients had taken appropriate antibiotic therapy, there was no difference in mortality rate between two groups. Also in our patients, between the antibiotic regimens and mortality rate were not significantly different [21]. Antibiotic treatment course for VAP is usually 7 days and it has been shown that this timing schedule has not been associated with higher mortality rate in comparison with longer periods [12].…”
Section: Discussionmentioning
confidence: 41%
“…However, similar results were obtained in our research (41.7 vs. 35.1). In a study between 2000 and 2003, the average residence days in hospitals following bacteremia of 112 patients with Acinetobacter bacteremia (32 days) were compared with 90 patients with bacteremia caused by Klebsiella pneumonia (22 days) and the difference was not significant, while the average of hospitalization days in our patients with MDR-AB VAPs was significantly more than that of the cases infected with ESBL-KP VAPs (42 days vs. 35 days) [21].…”
Section: Discussionmentioning
confidence: 87%
“…113 Hosoglu et al performed a casecontrol study in an ICU in Turkey that compared 95 patients with MDR-ABC infections to 95 controls without ABC colonization or infection. 114 Multivariate analysis identified only one risk factor for MDR-ABC infection; i.e., antibiotic use for more than 7 days (OR: 2.38, p ¼ 0.016). However, univariate analysis cited prior use of CPs (p ¼ 0.001) or glycopeptides (p ¼ 0.001) as risk factors for MDR-ABC infections.…”
Section: Abc Virulence Factors and Pathogenesismentioning
confidence: 97%
“…However, univariate analysis cited prior use of CPs (p ¼ 0.001) or glycopeptides (p ¼ 0.001) as risk factors for MDR-ABC infections. 114 A study in Thailand found that prior CP use was a strong risk factor for CRAB (OR: 5.20) as well as XDR (OR: 6.30) and PDR ABC (OR: 106). 115…”
Section: Abc Virulence Factors and Pathogenesismentioning
confidence: 99%
“…44 The carbapenem values (imipenem, meropenem, doripenem) has experienced some resistance to A. baumanii, P. aeruginosa, K. pneumoniae, The previous use of carbapenems makes bacteria is resistant, resulted in unsusceptible used. 52 According to the Infectious Disease Society of America (IDSA), the risk factors for MDR (Multi-Drug Resistant) in VAP are the previous use of intravenous antibiotics within 90 days, septic shock during VAP, acute respiratory distress syndrome before VAP, five or more days of hospitalization before the onset of VAP, replacement therapy of acute kidney before the onset of VAP. Meanwhile, the risk factor for MDR in HAP is the previous use of intravenous antibiotics within 90 days.…”
Section: Carbapenem Resistancesmentioning
confidence: 99%